Determination of hydric demand through the use of evaporimeters tanks (Research, Society and Development, 2022)
The efficient management of water in the current scenario of global water scarcity is a constant, in this sense, the search for ways to manage an irrigation system that value the economy of water resources is essential. Thus, the quantification of the water demand of cultures using evaporimeter tanks is increasingly in evidence, as it is an indirect and low-cost method, especially when it comes to alternative tanks. Thus, the objective of this work was to study the determination of water demand through the use of low cost evaporimeter tanks that can be applied in any agricultural property aiming at the rational management of irrigation in face of the problem of water scarcity. The bibliographic survey work in an academic database: Academic Google, Theses and Dissertations and books, Science and Science Direct, with keywords on or subject not lost from 1997 to 2021. Evaporimeters are efficient in quantifying the water requirement in different regions and cultures. Alternative Evaporimeters are inexpensive and can be used by large, medium and small producers on their properties. There are several works on the quantification of water demand in different cultures with the use of evaporimeters both nationally and internationally. Irrigation management using evaporimeter tanks can be low cost and accessible. Meeting the water demand of crops is essential to have good yields and avoid wasting water resources in the current scenario of scarcity.